2014
DOI: 10.1089/jmf.2013.2961
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Extracts Facilitate Bacterial Agglutination and Prevent Biofilm Formation on Orthodontic Wire

Abstract: Soybean is an essential food ingredient that contains a class of organic compounds known as isoflavones. It is also well known that several plant agglutinins interfere with bacterial adherence to smooth surfaces. However, little is known about the effects of soybean extracts or genistein (a purified isoflavone from soybean) on bacterial biofilm formation. We evaluated the effects of soybean (Glycine max) extracts, including fermented soybean and genistein, on streptococcal agglutination and attachment onto sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We set the effect size of 1.0, a power of 0.9, and a significance level of .05, which calculated our sample size to be 5. 14 Five healthy participants were recruited for the study. Inclusion criteria were as follows: (1) Subject population should consist of 3 women and 2 men with an average age of 26.5 (±2.20) years; (2) population should have both genders; (3) all ethnicities should be included; (4) complement of all permanent teeth from second molar to second molar; (5) no crowns, labial bondings, or laminates on designated teeth; and (6) good alignment of teeth.…”
Section: Experimental Design and Sample Size Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…We set the effect size of 1.0, a power of 0.9, and a significance level of .05, which calculated our sample size to be 5. 14 Five healthy participants were recruited for the study. Inclusion criteria were as follows: (1) Subject population should consist of 3 women and 2 men with an average age of 26.5 (±2.20) years; (2) population should have both genders; (3) all ethnicities should be included; (4) complement of all permanent teeth from second molar to second molar; (5) no crowns, labial bondings, or laminates on designated teeth; and (6) good alignment of teeth.…”
Section: Experimental Design and Sample Size Calculationmentioning
confidence: 99%
“…Porphyromonas gingivalis was grown in brain heart infusion (BHI) broth containing hemin and vitamin K at 37°C in an anaerobic chamber. 14 Aggregatibacter actinomycetemcomitans was grown in trypticase soy broth supplemented with yeast extract and glucose. The plates were inoculated at 37°C in 10% CO 2 for 48 hours.…”
Section: Bacterial Growth Mediummentioning
confidence: 99%
“…Particularly, some studies have described that specific compounds in the fabrication of orthodontic appliances can be related to the bacterial adherence of cariogenic bacteria associated with their manufacturing and complex design [ 45 ]. The SS has been identified as a material with a high potential for microbial adherence due to surface energy [ 72 , 73 ]; but also, it has demonstrated to have a low adherence affinity with S. mutans compared to other materials such as plastics and ceramics [ 74 ]. In addition, authors have reported that CuNiTi wire had higher levels of bacterial adherence compared to NiTi when they were exposed to the S. mutans strain, possibly due to differences in rougher surface and higher surface free energy [ 75 ].…”
Section: Discussionmentioning
confidence: 99%